Stenotrophomonas maltophilia isolate UPMKH2 with the abilities to suppress rice blast disease and increase yield a promising biocontrol agent - Fariman, Azadeh Badri; Abbasiliasi, Sahar; Abdullah, Siti Nor Akmar; Mohd Saud, Halimi; Wong, Mui Yun (Elsevier, 2022)
This study aimed to identify potential rhizobacteria from local rice fields for the control of blast disease. A total of 40 bacterial strains were isolated from rice roots and rhizospheres located in four major rice granaries in peninsular Malaysia and identified as Stenotrophomonas maltophilia based on cultural morphology on selective medium and 16S rDNA analysis. Based on dual culture and culture filtrate tests, UPMKH2 showed the highest percent inhibition of radial growth (PIRG), 64.2% and 95.8%, respectively. In an in vivo study, treatment of rice with UPMKH2 through seed treatment and foliar spray showed significant disease suppression with percent disease reduction (% DR) of 55.6 and 47.9%, respectively. Application of UPMKH2 using both methods increased yield components such as the panicle length, number of spikelet per panicle, and 100-grain weight as well as significantly increased growth promotion parameters such as shoot height, root length, number of tillers per hill, and shoot and root dry weight. Defense-related gene expression in rice leaves with UPMKH2 application via seed treatment and inoculated with P. oryzae using RT-qPCR showed that the target genes, β-1, 3- glucanase (Gns1) and chitinase (Cht-1) were increased compared to the untreated control. Taken together, these results showed that UPMKH2 is a promising candidate to be developed as a biocontrol agent for sustainable management of rice blast disease.